Isolation, Production, and Characterization of Thermotolerant Xylanase from Solvent Tolerant Bacillus vallismortis RSPP-15 - Rajeeva Gaur; Soni Tiwari; Priyanka Rai; Versha Srivastava (International Journal of Polymer Science)
Sixty bacterial strains isolated from the soils sample in the presence of organic solvent were screened for xylanase production. Among them, strain RSPP-15 showed the highest xylanase activity which was identified as Bacillus vallismortis. The isolate showed maximum xylanase production (3768 U/mL) in the presence of birch wood xylan and beef extract at 55°C pH 7.0 within 48 h of incubation. The enzyme activity and stability were increased 181.5, 153.7, 147.2, 133.6, and 127.9% and 138.2, 119.3, 113.9, 109, and 104.5% in the presence of Co2+, Ca2+, Mg+2, Zn+2, and Fe+3 ions (10 mM). Xylanase activity and stability were strongly inhibited in the presence of Hg and Cu ions. The enzyme was also stable in the presence of 30% of n-dodecane, isooctane, n-decane, xylene, toluene, n-hexane, n-butanol, and cyclohexane, respectively. The presence of benzene, methanol, and ethanol marginally reduced the xylanase stability, respectively. This isolate may be useful in several industrial applications owing to its thermotolerant and organic solvent resistance characteristics.